SMCE MODEL FOR COMMERCIAL AREAS SUITABILITY IN SERANG CITY - Muafiroh, Salsa; Wibowo, Adi (UI Scholars Hub, 2022)
Commercial areas refer to specific zones designated for business activities, such as trade, retail, and industry, which play a critical role in supporting regional economic development. In the case of Serang City, the government has planned its development as a hub for commerce and industry. However, selecting an optimal location for commercial areas involves addressing challenges related to multiple criteria and alternative options, each with varying advantages and trade-offs, which often complicates the decision-making process. This research aims to analyze spatial modeling using simulations based on the Spatial Multi-Criteria Evaluation (SMCE) method, supported by ILWIS software to determine the most suitable locations. The results indicate that simulations A, B, C, and D effectively identify areas suitable for commercial development. Among these, simulation C, which emphasizes carrying capacity and land use variables, proved most accurate, identifying a potential area of 7,042.02 hectares across Serang and Cipokjaya Regencies. The study concludes that the SMCE method offers a robust framework for developing simulation models that assist in policy decision-making. Future research is recommended to incorporate additional parameters to enhance the precision and comprehensiveness of determining the best commercial locations